ANALISIS KEPUASAN PENGGUNA PADA APLIKASI MyIM3 MENGGUNAKAN METODE UTAUT DIKALANGAN MAHASISWA UNIVERSITAS INDO GLOBAL MANDIRI - Nurkhalizah, Nyimas Ghefira; Heryati, Agustina; Alie, M. Fadhiel; Ghazali, K. (Jurnal Ilmiah Informatika Global, 2025)
The myIM3 application is a digital service designed to facilitate users in purchasing data packages, topping up credit, and checking quotas. Among students at Universitas Indo Global Mandiri Palembang, this application is used to support daily telecommunication needs. However, several issues are frequently reported, such as inconsistent application stability, slow service speeds, suboptimal user experiences with certain features, and delays in processing data package payments. These shortcomings can impact user satisfaction and the application's reputation. This study aims to analyze user satisfaction with the myIM3 application among students using the Unified Theory of Acceptance and Use of Technology (UTAUT) approach. Data were collected through surveys using a questionnaire based on the UTAUT model, covering four main variables: Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions. The data were analyzed quantitatively with the aid of statistical software. The findings identify factors affecting student satisfaction and provide recommendations for improving the application to better meet user needs.This research is expected to serve as a reference for the myIM3 application developers to enhance service quality and user satisfaction, particularly among students.